(untitled) (Canadian Hematology Today, 2025)
Chronic lymphocytic leukemia (CLL) and small lymphocytic lymphoma (SLL) are recognized as a single disease entity with distinct phenotypic manifestations, characterized by predominant peripheral blood (PB) involvement in CLL and nodal and/or splenic disease in SLL1-3. This article explores the historically divergent approaches taken to treat CLL and SLL, highlights recent advances in understanding their shared biology, and advocates for a unified approach to real-world management and clinical trial eligibility for both conditions.